THE INFLUENCE OF MENANTEA'S BRAND IMAGE & BRAND TRUST ON CUSTOMER LOYALTY AND CONSUMER SATISFACTION LEVELS - Lisnawaty, Rebecca Yemima; Alvita, Meilisa (Yayasan Education and Social Center, 2023)
This research aims to analyze the influence of brand image and brand trust on the level of customer loyalty, especially in the context of post-pandemic consumer satisfaction. This research involved 150 respondents who were Menantea consumers in the JABODETABEK area, using a combination of purposive sampling and probability sampling data collection techniques. The research results show that the Menantea brand image has a positive impact on brand trust, consumer satisfaction, and ultimately influences customer loyalty. Even though one hypothesis was rejected, the Menantea company continues to strive for innovation and other activities to maintain the level of consumer loyalty to the Menantea brand. These findings provide important insights for companies in designing post-pandemic marketing and brand management strategies to increase consumer satisfaction and strengthen customer loyalty